American Populism in the Context of Political Discourse: History and Vodernity - Kiyanka, Iryna (Mediaforum : Analytics, Forecasts, Information Management, 2023)
An important feature of populist political forces in the United States is the desire for widespread use of direct democracy mechanisms, such as referendums, local and national elections, direct elections, etc. It was mentioned above that the People's (Populist) Party already included relevant requirements in its program (in particular, the introduction of direct elections of senators, which was later implemented). In the political tradition of the United States, the roots of the plebiscitary, as opposed to representative, vision of democracy go back to the very founding of this country.